Didactic Models in the Teaching of the ABO System and the Rh Factor: A Review of the Methods and Factors that Influence Learning (Revista Brasileira de Pesquisa em Educação em Ciências, 2025)
The adoption of didactic models in the teaching of the ABO system and the Rh factor is an alternative for reducing the difficulties encountered by students in the learning process. The aim of this study was to gather up-to-date information, describing the types of didactic models and associating the conditioning factors that contribute to the teaching-learning process of the ABO system and the Rh factor. This is a scoping review, conducted following the recommendations of the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR). The study’s guiding question was constructed using the PCC strategy (population, concept and context) and searches carried out on the Dimensions platform, resulting in 289 articles, of which 8 samples were eligible for analysis. The use of didactic models made from recyclable materials, the construction of comic strips (HQs), as well as the implementation and programming of digital games applied in the learning process of the ABO system and the Rh factor, and in the teaching of genetics when it involves consanguinity, was verified. The samples revealed that the models adopted increase the power of assimilation of the content, making classes more dynamic by facilitating abstraction and contextualization, configuring themselves as expressive and reflective pedagogical strategies, allowing for the collective construction of knowledge, representing conditioning factors in the teaching-learning process, when methodological resources are implemented that involve genetics, the ABO system and the Rh factor, as up-to-date information in the teaching-learning process.